Hi! Could you help me out with this exercise? Thanks!


  1. 1
asked by Josh Garder
  1. Please use the same name for your posts.
    This is a pipe open at one end and closed at the other.
    Use the same acoustic (organ pipe) sites I gave you yesterday.

    posted by Damon enough already

Respond to this Question

First Name

Your Response

Similar Questions

  1. Physics

    I need help with this exercise, I don't even know where to start. imgur(dot)com/WDCikKK(dot)png
  2. Physics

    I need help with this exercise, any ideas how do impedances and resitance work in a smith chart? imgur(dot)com/sZAvj6y(dot)png
  3. Programming? Math?

    I have to compute the symbol coordinates and modulation constellation and I don't really know how to do that when I don't have a a cosines, but instead I have a square pulse. The exercise is the following one:
  4. Physics

    Hi, I need some guidance solving this, thank you very much! imgur(dot)com/JCfHa13(dot)png
  5. Physics

    Hi! Could you help me with this question? imgur(dot)com/lJk2Mfa(dot)png
  6. Calculus

    This is the question: i[dot]imgur[dot]com/EHneTuB[dot]jpg Am i correct in simply adding 1 + (-3), and equates to (-2) being the answer.
  7. Physics

    i41 tinypic com/2qna74k png (add the periods) For the vectors in the figure, with a = 6.4, b = 2.5 and c = 6.87. Calculate a(dot)b calculate a(dot)c calculate b(dot)c I got 0 for a(dot)b but the same method (ac*cos(theta)) does
  8. Physics

    I have to fill the following table, I know it should only be applying formulas, but I'm not sure which formulas should I apply in every section. I would like to know which is the difference between the conductivity in Siemens per
  9. Math - Vectors

    If "u = (2,2,-1)", "v = (3,-1,0)" and "w = (1,7,8)", verify that "u (dot) (v + w) = u (dot) v + u (dot) w". My work: LHS: u (dot) (v + w) = (2,2,-1) (dot) (4,6,8) = [(2,2,-1) (dot) (3,-1,0)] + [(2,2,-1) (dot) (1,7,8)] = [u (dot)
  10. Vectors: Dot product

    Given a and b unit vectors if |a+b|=square root 3, determine (2a-5b)dot(b+3a) First I foiled the whole thing: =2(a dot b)+ 6 (a dot a) - 5(b dpt b) -15(a dot b) =-13(a dot b) + 6(a dot a) - 5(b dot b) =-13(1)(1)+6-5 =-13+1 =-12

More Similar Questions